2007
DOI: 10.1038/sj.mt.6300155
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Killing of Malignant Glioma by Bone Marrow–derived Tumor-Infiltrating Progenitor Cells Expressing a Suicide Gene

Abstract: Adult stem cells are promising cellular vehicles for therapy of malignant gliomas as they have the ability to migrate into these tumors and even track infiltrating tumor cells. However, their clinical use is limited by a low passaging capacity that impedes large-scale production. In the present study, a bone marrow-derived, highly proliferative subpopulation of mesenchymal stem cells (MSCs)-here termed bone marrow-derived tumor-infiltrating cells (BM-TICs)-was genetically modified for the treatment of malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(75 citation statements)
references
References 39 publications
1
72
0
2
Order By: Relevance
“…Meanwhile, they showed that the presence of this bystander effect is correlated with the expression of Cx43 in untransduced glioma target cells. Furthermore, Miletic et al 24 confirmed the gap junction communication between bone marrow (BM) and tumorinfiltrating cells (TICs) (a highly proliferative subpopulation of bone marrow-derived mesenchymal stem cells) and 9L cells. Their cell culture experiments showed that BM-TIC-TK cells exert a strong bystander effect on 9L glioma cells on GCV treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, they showed that the presence of this bystander effect is correlated with the expression of Cx43 in untransduced glioma target cells. Furthermore, Miletic et al 24 confirmed the gap junction communication between bone marrow (BM) and tumorinfiltrating cells (TICs) (a highly proliferative subpopulation of bone marrow-derived mesenchymal stem cells) and 9L cells. Their cell culture experiments showed that BM-TIC-TK cells exert a strong bystander effect on 9L glioma cells on GCV treatment.…”
Section: Discussionmentioning
confidence: 97%
“…MSCs have been shown to migrate toward gliomas (9) and track microscopic tumor deposits and infiltrating tumor cells in the brain (10,11). Furthermore, engineered MSCs have been shown to exert potent inhibition of tumor growth in an in vivo glioma model and also exhibit a protective effect for the normal brain (12).…”
mentioning
confidence: 99%
“…Bystander effects were observed after intratumoral administration of MSCs and intraperitoneal injection of gancyclovir, with a significant fraction of mouse model animals surviving long-term period [99]. A novel and worth mentioning aspect of this study was the use of imaging techniques PET and MRI to track the injected cells and the possibility of determinate the therapeutic efficacy.…”
Section: Recently Published Patents (2012-present) Concerning Mscs Asmentioning
confidence: 99%
“…Prepare a conditioned extracellular medium as an apoptosis-modulating cell-free composition [92] MSCs particles Particles (vesicle or exosome) possess biological properties of a MSC [95] Expressing a suicide gene High selective anticancer effects (conversion of a prodrug to an anticancer agent at the cancer site) [98][99][100][101][102] Micro carriers for protein delivery Deliver large quantities of the therapeutic agent for extended periods of time [104,105] Secreting TRAIL Inducing apoptosis and inhibition of tumor growth [108,[114][115][116] Delivering of oncolytic viruses Induction of apoptosis [117] Engineered MSCs for secretion of antibody-like molecules Can lead to elimination of early cancer cell metastasis [118] With a number of target therapeutics currently under development as anticancer therapy, not only cancer cells, but also cells from the microenvironment (endothelial cells or MSCs) are targeted. This therapeutic approach may have many adverse effects associated with the elimination of cells not involved in cancer progression or in chemoresistance.…”
Section: New Facts Raised Concerns About Use Of Mscs As An Anticancermentioning
confidence: 99%